LGG-14. THE GENETIC LANDSCAPE OF DYSEMBRYOPLASTIC NEUROEPITHELIAL TUMORS - Jain, Payal (Neuro Oncol, 2019)
Classic dysembryoplastic neuroepithelial tumor (DNT) is a low-grade pediatric neoplasm defined histologically by specific glioneuronal elements with mucin-matrix floating neurons. However, many tumors preclude confident morphologic classification and are better designated as mixed neuronal-glial tumors (MNGTs). To determine if a molecular signature is associated with classic DNT morphology, we retrospectively examined the histological, genetic and molecular profile of a DNT/MNGT cohort. In this multi-institutional study, 34 patients with DNT (11) and MNGT (23) were included. Methodology included combinations of fusion detection by anchored multiplex PCR or RNA sequencing, sequence alterations in 238 cancer gene panel or whole genome by next generation sequencing (NGS), and copy number variants (CNVs) by genome wide array or NGS. A novel fusion was characterized by generating NIH3T3 stable cells for pathway analysis and transformation assays. Based on genetic profiles, tumors were classified as follows: ‘BRAF-altered’ included 23% (8/34) with BRAF V600E or BRAF-fusions; ‘FGFR-altered’ included 20.5% (7/34), where we further characterized the rare FGFR2-CTNNA3 fusion; ‘Other alteration’ encompassed 26% (9/34) with NTRK2 fusion, KDM5C and PDGFRA mutations or CNVs; ‘no alteration’ included 29% (10/34) with no known pathogenic mutations (variants of unknown significance excluded). Three patients had potential cancer predisposition syndromes (ATMx2, NF1). In cell models, FGFR2-CTNNA3 was an oncogenic driver activating MAPK/PI3K pathways. Overall, we found genetic alterations affecting MAPK/PI3K pathways in 44% (15/34) of tumors, including 20.5% with gene fusions. Given the spectrum of abnormalities and small cohort size, a definitive genetic profile distinguishing classic DNT from MNGT was not identified. However, all the BRAF-altered cases exhibited MNGT histology, whereas the other 3 sub-groups spanned both histologies. The BRAF-altered group also showed recurrence free survival (maximum follow-up of 60 months). This study highlights the genetic diversity prevalent across DNT/MNGT and the difficulty of assigning a molecular classifier to this tumor group.